Equilibria with Unemployment in Segmented Labor Markets - Demekas, Dimitri (IMF Working Papers; Working Paper ;, 1990)
The paper proves four theorems in an n-sector model of a segmented labor market, with search costs, and a continuum of workers with different reservation wages, who can apply to any number of sectors. The main conclusions are that: (i) an equilibrium with unemployment always exists; and (ii) some of the unemployment is involuntary, in the sense that it consists of workers with reservation wages below the equilibrium wage in the secondary market. These conclusions hold in the case of both separate and non-separate markets.